2001
DOI: 10.1021/bi002555c
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Environmental Factors on the Kinetics of Insulin Fibril Formation:  Elucidation of the Molecular Mechanism

Abstract: In the search for the molecular mechanism of insulin fibrillation, the kinetics of insulin fibril formation were studied under different conditions using the fluorescent dye thioflavin T (ThT). The effect of insulin concentration, agitation, pH, ionic strength, anions, seeding, and addition of 1-anilinonaphthalene-8-sulfonic acid (ANS), urea, TMAO, sucrose, and ThT on the kinetics of fibrillation was investigated. The kinetics of the fibrillation process could be described by the lag time for formation of stab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

88
1,365
1
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,117 publications
(1,455 citation statements)
references
References 51 publications
88
1,365
1
1
Order By: Relevance
“…72 In fact, the influence of agitation can be so profound that, in the case of insulin, it was found to attenuate the effects of other parameters, such as protein concentration and ionic strength, that influence the kinetics of amyloid fibril assembly. 68 …”
Section: Protein Aggregationmentioning
confidence: 99%
“…72 In fact, the influence of agitation can be so profound that, in the case of insulin, it was found to attenuate the effects of other parameters, such as protein concentration and ionic strength, that influence the kinetics of amyloid fibril assembly. 68 …”
Section: Protein Aggregationmentioning
confidence: 99%
“…Enhanced formation of different protein fibril systems by addition of preformed fibrils (seeding) has previously been established. [16][17][18] Another possibility is inducing a mechanical disturbance in the system. In insulin solutions, continuous agitation was shown to enhance the fibril formation.…”
Section: Introductionmentioning
confidence: 99%
“…In insulin solutions, continuous agitation was shown to enhance the fibril formation. 17 Unfortunately, these experiments were not performed in a well-defined flow field. Stathopulos et al 18 found that sonication of a diverse group of proteins resulted in the formation of fibrils.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The nucleation step is known to have a high activation energy barrier, which results in a distinct lag phase during assembly kinetics [10]. Various environmental factors such as pH, ionic strength and the presence of seeds affect the lag phase of amyloid assembly [11,12]. In addition to studies in bulk solution, amyloid formation on surfaces has been actively investigated since it may more closely mimic physiological environments such as cell membrane [13].…”
Section: Amyloid Nanofibermentioning
confidence: 99%